PENGARUH PENGENDALIAN INTERNAL, WHISTLEBLOWING, DAN ETHICAL LEADERSHIP TERHADAP PENCEGAHAN FRAUD (STUDI EMPIRIS PADA KANTOR PERWAKILAN BPKP JAWA TENGAH) - Hasna Syafira; Anis Chariri (Diponegoro Journal of Accounting, 2023)
This research was conducted in order to examine various factors that influence fraud prevention in public sector organizations, in this case organizational factors consisting of internal control, whistleblowing, and ethical leadership. The three organizational factors are related to each element contained in the fraud triangle theory. The data used in this research are primary data obtained using the survey method by distributing questionnaires to employees of Representative Office of Financial and Development Supervisory Agency in Central Java. Respondents were asked to provide their perceptions of the statement in the questionnaire which were described on a scale of 1 (one) to 5 (five). The data is then processed using multiple linear regression in order to obtain final conclusions from predetermined hypotheses. This study shows that internal control, whistleblowing, and ethical leadership significantly influence fraud prevention. Through these results it can be concluded that all organizational factors tested in this study are in accordance with all elements stated in the fraud triangle theory.